High-efficiency all-inorganic full-colour quantum dot light-emitting diodes. (April 2018) - Yang, Xuyong; Zhang, Zi-Hui; Ding, Tao; Wang, Ning; Chen, Guo; Dang, Cuong; Demir, Hilmi Volkan; Sun, Xiao Wei
Abstract: All-inorganic quantum dot light-emitting diodes (QLEDs) with excellent device stability have attracted significant attention for solid state lighting and flat panel display applications. However, the performance for the present all-inorganic QLEDs is far inferior to that of the well-developed QLEDs with organic charge transport layers. Our all-inorganic full-colour QLEDs show the maximum brightness and efficiency values of 21, 600 cd/m 2 and 6.52%, respectively, which are record-breaking among the existing all-inorganic QLEDs. The outstanding performance is achieved by an efficient design of device architecture with solution-processed charge transport layers (CTLs). Meanwhile, the ultrathin double-sided insulating layers are inserted between the quantum dot emissive layer and their adjacent oxide electron transport layers to better balance charge injection in the device and reduce the quenching effects for inorganic CTLs on QD emission. This study is the first account for high-performance, all-inorganic QLEDs insightfully offering detailed investigations into the performance promotion for inorganic electroluminescent devices. Graphical abstract: High-performance, full-colour, all-inorganic QLEDs have been demonstrated by the use of solution-processed charge transport layers and the insertion of double-sided insulating thin layers between the quantum dot (QD) layer and their adjacent oxide electron transport layers. The efficiency reaches 6.52%, the highest value reported for all-inorganic QLEDs.fx1